`13)`
`5x-2y-(2x+1).(2y-5x)`
`=(5x-2y)+(2x+1).(5x-2y)`
`=(5x-2y).(1+2x+1)`
`=(5x-2y).(2+2x)`
`=(5x-2y).2.(1+x)`
`14)`
`3-2x+(2x-1).(2x-3)`
`=(3-2x)-(2x-1).(3-2x)`
`=(3-2x).[1-(2x-1)]`
`=(3-2x).(1-2x+1)`
`=(3-2x).(2-2x)`
`=(3-2x).2.(1-x)`
`15)`
`(2-x)^2-(x+1).(x-2)`
`=(2-x)^2+(x+1).(2-x)`
`=(2-x).(2-x+x+1)`
`=(2-x).3`
`16)`
`(3x+2)^2-(2+3x)(x-1)`
`=(3x+2)^2-(3x+2).(x-1)`
`=(3x+2).[3x+2-(x-1)]`
`=(3x+2).(3x+2-x+1)`
`=(3x+2).(2x+3)`
`17)`
`(x-5)^2+(3x-1).(5-x)`
`=(x-5)^2-(3x-1).(x-5)`
`=(x-5).(x-5-3x+1)`
`=(x-5).(-2x-4)`
`=-2.(x-5).(x+2)`
`18)`
`4x^2-4x-y^2+1`
`=(4x^2-4x+1)-y^2`
`=(2x-1)^2-y^2`
`=(2x-1-y).(2x-1+y)`
`19)`
`x^2-2xy+y^2-z^2+2zt-t^2`
`=(x^2-2xy+y^2)-(z^2-2zt+t^2)`
`=(x-y)^2-(z-t)^2`
`=[(x-y)-(z-t)].[(x-y)+(z-t)]`
`=(x-y-z+t).(x-y+z-t)`
`20)`
`6x^2+7x-3`
`=6x^2-2x+9x-3`
`=2x.(3x-1)+3.(3x-1)`
`=(2x+3).(3x-1)`
`21)`
`(5-3x).(2x+3)-15+9x`
`=(5x-3x).(2x+3)-3.(5x-3x)`
`=(5x-3x).(2x+3-3)`
`=(5x-3x).2x`